Kinematic Analysis of Head and Trunk of Elderly Subjects during Climbing of Stairs and a Ramp - Lee, Sang-Yeol; Ha, Kyoung-Jin; Han, Jin-Tae; Kim, Young-Mi (Journal of Physical Therapy Science, 2013)
[Purpose] The purpose of this study was to investigate the kinematic adaptation of the head and trunk of elderly subjects in the ascent of stairs and ramp. The three-dimensional kinematic patterns of the head and trunk were examined during stairs and steep ramp climbing. [Methods] The subjects of this study were 14 elderly people who had no musculoskeletal disease, or low back pain, and who showed normal ROM. Kinematic data were collected using the 6-camera Vicon system (Oxford Metrix, Oxford, England). Repeated measures ANOVA analysis was used to investigate the effect of gait mode on kinematics of the head and trunk. [Results] The results of our study show that the angle of the trunk during ascent of stairs and a ramp was modified in sagittal, frontal and transverse plane. The angle of the head and neck during ascent of stairs and a ramp did not change in the sagittal plane but changed in the frontal and transverse planes. [Conclusion] This study investigated and discusses some basic kinematic mechanisms underlying the pattern of movements of the head and trunk of elderly subjects during ascent of stairs and a ramp. We showed that postural adaptation of head and trunk is necessary for balance.